Changes in neutrophile-to-lymphocyte ratio as predictive and prognostic biomarker in metastatic prostate cancer treated with taxane-based chemotherapy - Neuberger, Manuel; Weiß, Christel; Goly, Nora; Skladny, Janina; Nitschke, Katja; Wessels, Frederik; Kowalewski, Karl-Friedrich; Waldbillig, Frank; Hartung, Friedrich; Nientiedt, Malin; Egen, Luisa; Herrmann, Jonas; et al. (Discover oncology, 2022)
Objectives: To assess the predictive and prognostic value of changes in longitudinal neutrophile-to-lymphocyte (NLR) ratios in men receiving taxane-based chemotherapy for metastatic prostate cancer (PC). Methods: Retrospective, unicentric cohort study of patients treated with either docetaxel for metastatic hormone-sensitive PC (mHSPC) or docetaxel or cabazitaxel for metastatic castration-refractory PC (mCRPC) at a tertiary referral hospital between 2010 and 2019. NLR ratios were calculated for each cycle. Next, slopes over the first three (NLR3) and over six cycles (NLR6) were calculated and analysed for biochemical/radiologic response and survival. Results: A total of 36 mHSPC (docetaxel), 118 mCRPC (docetaxel) and 38 mCRPC (cabazitaxel) patients were included. NLR3 was significantly associated with 1-year-survival, radiographic and biochemical response in mCRPC (docetaxel) in uni- and multivariable analyses. In mCRP (docetaxel), positive NLR3s were associated with favourable 1-year-survival. Conclusion: This study demonstrated NLR3 as a prognostic marker in men receiving docetaxel for mCRPC. NLR3 might be a clinical tool to reflect the individual’s response to taxane-based chemotherapy. Thereby, NLR3 could complement existing biomarkers and help to early identify treatment failure before complications arise. Further prospective and multicentric studies are needed to extend and confirm the presented results.